Jute/glass reinforced polyester resin laminated composite by compressive moulding mechanical properties based on different stacking sequence and surface treatment - Abait, Siti Fatimah (2014)
Effect of stacking sequence, NaOH and silane treatment on tensile and flexural properties of jute glass fibre polymer composites have been evaluated experimentally. Jute fibres were subjected to 5% NaOH solution treatment for 24 hours and 1 % of silane solution treatment at 2 hours. All laminates with a 5 total plies, by varying the number and sequence of glass and jute fibre as to obtain 6 different stacking sequences. All jute and all glass fibre also had been prepared for the comparison purpose. Laminate were fabricated by compressing method at 40°C for 30 minutes, followed by curing at room temperature for 24 hours. Specimen preparation and testing was conducted as per ASTM standards. A test was conducted using an Instron UTM machine at room temperature. The result indicated that the suitable laminating hybrid configuration of the composite by placing fibre mat at different sequence and stack could improve the mechanical properties. An overall comparison, the hybrid composite with 3 plies of glass fibre treated with NaOH was the optimum combination with a good balance between properties and cost.